Rotatripsy: synergistic effects of complementary technologies: a case report. Issue 4 (17th April 2021) - Kaur, Navjyot; Pruthvi, C R; Sharma, Yashpaul; Gupta, Himanshu
Abstract: Background: Percutaneous coronary intervention (PCI) to calcified coronary lesions (CCLs) remains one of the most complex procedures. Latest modality to modify calcium, intravascular lithotripsy (IVL), has shown good safety and efficacy in preliminary research. However, it may be associated with acute complications, and as standalone therapy, is not sufficient for all CCLs. Case summary: Eighty-two-year-old man, known case of coronary artery disease and multiple comorbidities, presented with worsening angina of 1 month duration. Coronary angiography revealed heavily calcified triple vessel disease with critical distal left main (LM) involvement. Owing to high surgical risk, he was offered intravascular ultrasound (IVUS) guided PCI with intra-aortic balloon support. While the diffuse, circumferential calcified lesions in LM and left anterior descending (LAD) artery were modified with rotablation (RA) followed by IVL with 3.5 and 3.0 mm balloons; ostial-proximal lesion in left circumflex (LCX) artery was treated with 3.0 mm IVL balloon as a standalone therapy. During second cycle of shockwave therapy in LCX, the 3.0 mm IVL balloon ruptured with type C dissection extending upto LM ostium which required emergent LM bifurcation stenting. We had a good angiographic result which was confirmed with IVUS. Discussion: ntravascular lithotripsy and RA are complementary technologies in treating CCLs. Rotablation with a relatively small-sized burr is safe and can favourably modify superficial calcium which helps in smooth delivery of IVL balloon and ensures safe shockwave therapy, if required. Unselected upfront use of IVL without intravascular imaging may be associated with complications as described in this case.